Cost of Preliminaries of Construction Projects for Civil Infrastructure Works in Malaysia (Sains Humanika, 2017)
The preliminaries bill for quantities of a construction project provides general information, mandatory instructions, and setup running costs for a construction contract period. The bill is crucial and arbitrary in nature. The aim of this study is to verify the percentage difference between preliminaries of building and civil infrastructure works. The objective is to assist players in the construction industry to differentiate the preliminaries percentage between both types of civil works. As such, the decision maker would be able to make a more reliable budget allocation, particularly for the civil infrastructure project. 25 tender evaluation documents from six civil infrastructure tender evaluation exercises were analysed. The average preliminaries were derived based on the qualitative method using content analysis. The preliminaries for building works established by previous researchers and civil infrastructure derived from this study were compared to verify any significant deviation. The statistical analyses using Boussabaine's Â and standard deviation were compared to establish the most reliable result. The study concludes that the preliminaries of civil infrastructure works are between 3.26% and 6.38% as compared to that of building works between 3.60% and 7.94%. Consequently, the preliminaries of civil infrastructure work are lower up to 16.5% as compared to the building work. Despite the differences, average preliminaries are higher than 3% but not exceeding 10% of the tender sum for both types of construction works. Thus, the findings provided significant updates for the Malaysian construction industry.Â
Keywords: Civil infrastructure; building work; preliminaries; tender evaluation